Most dangerous : Daniel Ellsberg and the secret history of the Vietnam War - Sheinkin, Steve (2015)
"The story of Daniel Ellsberg and his decision to steal and publish secret documents about America's involvement in the Vietnam War"--
Prologue: Feasibility Study -- Part I. Insider -- Part II. Secrets and Lies -- Part III. Outsider -- Epilogue: History Repeats.
Includes bibliographical references and index.
Ages 10 to 14.
Keywords: Pentagon Papers; Ellsberg, Daniel; Rand Corporation; United States; Vietnam; United States; Juvenile literature; Employees -- Biography -- Juvenile literature; Juvenile literature; Whistle blowing -- United States -- History -- 20th century -- Juvenile literature; Vietnam War, 1961-1975 -- United States -- Juvenile literature; JUVENILE NONFICTION / History / United States / 20th Century; JUVENILE NONFICTION / History / Military & Wars; JUVENILE NONFICTION / Biography & Autobiography / Historical; Foreign relations -- Vietnam -- Juvenile literature; Foreign relations -- United States -- Juvenile literature..; Politics and government -- 1969-1974 -- Juvenile literature